The reuse of technological resources in parliaments - Pereira González, Manuel (Journal of the Basque Parliament, 2023)
Carrying out the digital transformation of parliaments successfully requires joining the model of sharing and reusing technological resources among public administrations. The possibility that parliamentary administrations enjoy total technological autonomy is addressed, reflecting on its nature, to conclude that such autonomy is not possible in practice since there are interdependencies inherent to the very conception of technology. For this reason, a series of recommendations are proposed to anticipate that a computer failure may affect parliamentary activity, with preventive measures and the establishment of alternative plans. Pointing out the need to share technology between administrations, the different mechanisms that exist for this are presented, with examples of the different ways of sharing: source code, infrastructures, services, tools and data. Finally, we talk about the possible evolution of technology in parliamentary administration thanks, in part, to the help of disruptive technologies such as artificial intelligence and its recent applications.